Investigating the effect of thermal cycling on thermal characteristics of the nano-silica based phase changing material (PCM). (2022) - Saravanakumar, P.T.; Arunkumar, S.P.; Brailson Mansingh, B.; Manoj Kumar, P.; Subbiah, Ram; Eswarlal, Vimal Kumar
Abstract: Reliable thermal storage has become a critical factor for renewable energy-based thermal systems such as solar thermal collectors, because the incoming energy is inconsistent with time and, hence, an efficient energy management mechanism is required. Therefore, the collection of maximum possible energy during their availability and their uniform distribution during the lagging period has been the topic of research in recent times. The nano-enhanced phase changing materials (nano-PCMs) are recognized to be the eminent energy storage materials in terms of their thermal storage characteristics. However, their reliability over the period of thermal cycles is yet again in an interrogation. In this work, the nano-silica based paraffin was prepared through the dispersion of nano-silica in paraffin at three different lower volume fractions (0.5 vol%, 1.0 vol% and 2.0 vol%). Then, the thermal consistency and thermal properties of nano-silica/PCM such as latent heat, melting and solidifying temperatures were investigated using different instruments, namely thermogravimetric analyzer (TGA) and differential scanning calorimetry (DSC) after initial preparation and after 100 thermal cycles. The findings evidence that the nano-silica/PCMs are having good thermal consistency even after 100 thermal cycles up to a volume fraction of 1.0%. The deterioration of the properties has become prominent after 1.0% volume of nano-silica in paraffin.